Analysis of Visual Elements of YouTube Videos as a Medium for Teach Character Values in Children - Soetio, Dylan Sebastian; Wardaya, Marina (ULTIMART Jurnal Komunikasi Visual, 2025)
Digital Natives, the new generation of kids who have had an early exposure to digital tech since childhood and have since grown alongside technological advancements of the early 21st century. These advancements would be the rise of digital platforms such as YouTube, a collective digital network purpose-built for children for entertainment, play, and learning. Digital content produced provides various visual stimuli, such as characters and gestures, colors and shapes, and backgrounds to convey cohesive storytelling. However, the majority of content available hadn’t provided a positive impact due to the purposefulness to provide meaning and impact, or lack thereof. The premature approach taken by creators would lead to a decline in attention spans, negative ethics, and poor cognitive capacity in children’s development. The purpose of this research is to analyse visual elements and storytelling in media targeted to children on YouTube as a medium to implement moral ethics, train cognitive thinking, while preserving the attention spans of children. Qualitative descriptive methods and the theory of Semiotics by Roland Barthes are utilized in unison. The primary data obtained through direct Interviews with Parents and their children, with secondary data from Observation and Documentation. Research results present visual elements are simple, communicative, and supportive narration which convey emotion, stimulate empathy from children, honesty, and accountability. Findings suggest the importance of communicative design in creating digital content that not only peaks interest but also functions in improving cognitive capacity and creating a positive character.